Merancang Evaluasi Pendidikan Agama Islam yang Efektif: Penelitian - Ega Putri Handayani; Remiswal; Khadijah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article discusses the importance of designing effective evaluation in Islamic Religious Education (PAI). The aim of thi study is to examine the function, objectives, scope and targets, types, and development models of PAI evaluation that are relevant and applicaple. The research method used is library research by reviewing various relevant academic sources. The findings indicate that evaluation in PAI should not only focus on cognitive aspects but must also equally consider affective and psychomotor dimensions. Effective evaluation can be designed through various approaches, including the Tyler Model, CIPP, Competency-Based Evaluation, Holistic, Contextual, Authentic, and Project-Based Assessment. Furthermore, the success of evaluation depends on the timing and techniques used. With well designed evaluation, religious education becomes not only a process of knowledge transfer but also a transformation of values and character building of students comprehensively.